Keberhasilan inseminasi buatan menggunakan semen sexing beku pada Sapi Persilangan Ongole - Dwi Susan Setiyani; Aulia Puspita Anugra Yekti; Kuswati Kuswati; Trinil Susilawati (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2018)
The Artificial Insemination (AI)  results in Beef cattle are expected to be male calf because they can increaseweight gain rapidly, so in this study AI was carried out by using sexing semen with Percoll density gradient centrifugation method containing Y sperm.This study was conducted to evaluate the success rate of AI using frozen sexing semen on Ongole Cross Breed. The study method used wasexperimental, comparing AI frozen sexing semen and frozen semen in 54 Ongole Cross Breed. The study variableswere Non Return Rate1 (NRR1), Non Return Rate2 (NRR2) and Conception Rate (CR).The study showed that the success rate of based on the value of NRR1 and NRR2AI using frozen sexing semen on Ongole Cross Breed is lower than un sexed frozen semen with the NRR1 value is 73,91%; 93,54% while the value of NRR2 was 69,56%; 83,87%. Based on CR value of frozen sexing semen higher than un sexed frozen semen showed CR valuewas 43,47%; 35,48%.